2005
DOI: 10.4049/jimmunol.175.11.7738
|View full text |Cite
|
Sign up to set email alerts
|

Effector Function of Diabetogenic CD4 Th1 T Cell Clones: A Central Role for TNF-α

Abstract: Effector function of T cells in autoimmune diabetes has been widely studied with mixed populations of lymphoid T cells stimulated ex vivo, but this approach does not permit evaluation of the contribution by a single T cell clone in the inflammatory site during pathogenesis. We have investigated cytokine production both in vitro and in vivo in a panel of diabetogenic CD4 Th1 T cell clones derived from the NOD mouse. SuperArray analysis showed a common pattern of mRNA expression for inflammatory cytokines and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 25 publications
(20 reference statements)
7
50
0
Order By: Relevance
“…Neutralization of TNF-␣ blocked disease development after transfer of diabetogenic CD4 ϩ T cells into RIP-mI B␣/NOD mice. Consistent with our results, a recent paper (45) showed that diabetogenic CD4 ϩ T cells produce TNF-␣ and IFN-␥, which are highly representative of cytokines in natural T1D. Furthermore, targeted disruption of IL-1 receptor (46), caspase-1, which converts pro-IL-1␤ to active IL-1␤ (47) or iNOS (J. Fenyk-Melody and J. S. Mudgett, personal communication) have little protective effects on the development of T1D in NOD mice.…”
Section: Discussionsupporting
confidence: 82%
“…Neutralization of TNF-␣ blocked disease development after transfer of diabetogenic CD4 ϩ T cells into RIP-mI B␣/NOD mice. Consistent with our results, a recent paper (45) showed that diabetogenic CD4 ϩ T cells produce TNF-␣ and IFN-␥, which are highly representative of cytokines in natural T1D. Furthermore, targeted disruption of IL-1 receptor (46), caspase-1, which converts pro-IL-1␤ to active IL-1␤ (47) or iNOS (J. Fenyk-Melody and J. S. Mudgett, personal communication) have little protective effects on the development of T1D in NOD mice.…”
Section: Discussionsupporting
confidence: 82%
“…It shares many of the genetic and immunological features of the human disease, including the presence of diabetogenic T cells and spontaneous development of diabetes. The T1D model using adoptive transfer of NOD BDC2.5 T cells is well established (22,36). CD4 ϩ T cells play a key role in diabetogenesis, and their ability to cause diabetes in adult NOD SCID mice is accelerated when the mice are pretreated with cyclophosphamide (20), and this allowed us to observe infiltrating T cells at an early and predictable time after injection.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 ϩ T cells play a key role in diabetogenesis, and their ability to cause diabetes in adult NOD SCID mice is accelerated when the mice are pretreated with cyclophosphamide (20), and this allowed us to observe infiltrating T cells at an early and predictable time after injection. Activated BDC2.5 T cells of both Th1 and Th2 type can rapidly induce diabetes in NOD SCID (22,37). This model, although artificial, created a useful platform for optimizing the quantitative aspects of these techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall the significant effect of perforin deficiency points overwhelmingly to its dominant role in CTL-mediated beta-cell destruction in vivo (Figure 2, Table 1). Perforin deficiency does not reduce diabetes mediated by CD4 + T cells, demonstrating this is unlikely to be a dominant effector mechanism utilized by CD4 + T cells [94,95]. The main function of perforin is to facilitate the activation and delivery of granzymes into the target cell.…”
Section: Perforin and Granzymes Released By Ctls Are The Dominant Effmentioning
confidence: 99%